An epigenetically controlled PML/Slit axis at the root of cell migration in both normal and neoplastic cells in the CNS. (31st January 2018) - Deli, A; Amodeo, Valeria; Betts, Joanne; Bartesaghi, Stefano; Vouri, Mikaella; Roshani, Rozita; Galavotti, Sara; Zhang, Ying; Ellis, Matthew; Lau, Joanne; Oberndorfer, Sarah; Leite, Ana; et al.
Abstract: In the central nervous system (CNS), regulation of nuclear function has been implicated in the control of cell cycle and migratory processes during neurogenesis. Alterations of these processes can lead to neoplastic transformation of neural stem cells (NSCs) and glioblastoma multiforme (GBM). The ability of GBM cells to migrate through the brain parenchyma represents a key factor underlying GBM aggressiveness and resistance to treatment. Notably, brain cancer cells use the same routes utilized by neuroblasts/immature neurons and NSCs, suggesting a neurobiological root of brain cancer migration. However, our understanding of potentially common mechanisms regulating cell migration/invasion during neurogenesis and brain tumourigenesis remains limited. Our previous work has implicated the Promyelocytic Leukaemia protein (PML), the essential component of the PML nuclear body (PML-NB), in regulation of embryonic neurogenesis via its ability to control proliferation in NSCs. We set out to investigate the role of PML in adult neurogenesis and GBM. Loss of PML leads to impaired NSC and neuroblast migration and to a smaller olfactory bulb in the adult mouse brain. A similar migration defect is observed in primary GBM cells where PML expression has been knocked down. Mechanistically, PML controls cell migration in both mouse NSCs and primary GBM cells via down-regulation of Slit genes, which are key regulators of axon guidance during development. Changes in Slits transcription upon PML kd are caused by global reduction of the repressive H3K27me3 epigenetic mark. This is associated with its redistribution to nuclear lamina-associated domains (LADs). Finally, PML controls tumor invasion and survival in an orthotopic animal model and inversely correlates with patient prognosis in GBM. Taken together, these findings support a model whereby PML-mediated modifications of chromatin structure and function regulate cell migration during normal neurogenesis and brain tumorigenesis, suggesting a neurobiological root of brain cancer invasion.